ANALISA KELAYAKAN SIMPANG EMPAT TAK BERSINYAL MENGGUNAKAN MANUAL KAPASITAS JALAN INDONESIA - Sugeng Yani Widodo; Yosef Cahyo; Sigit Winarto; Agata Iwan Candra (Faculty of Engineering, Kadiri University, 2020)
The transportation problem is one of the main issues that are difficult to solve in several big cities. When congestion occurs, it can disrupt community activities. We already know that